Rhetorical view of corporate legitimacy / Mahadir Ladisma @ Awis, Hazman Shah Vijayan Abdullah and Norziana Lokman - Ladisma@Awis, Mahadir; Abdullah, Hazman Shah Vijayan; Lokman, Norziana (Universiti Teknologi MARA, Shah Alam, 2017)
Recent development in understanding corporate legitimacy has heightened the needs for corporate to believe that the corporation activities affect not only how stakeholder act towards organizations, but also how they understood them. It is also perceived that legitimate organization not only as worthier, but also as more meaningful, more predictable, and more trustworthy. This paper highlights an important element of corporate legitimacy. The term legitimacy itself indicates the credibility of corporations which giving them more privilege to gain access on their resources. However, the fluctuating demands, perception and complex expectations from the stakeholders greatly contributed to the chaotic status quo within the organization. Thus, it is imperative for the corporation to understand the different types of corporate legitimacy that will implicate their survival. The notion of legitimacy which claimed as gaining acceptance of society, compliance with norms, values, beliefs and definition is still an important standpoint in institutional and strategic approach. Clearly, legitimacy is socially constructed and that it reflects the congruence between the expectation and norms of significant social groups; thus, legitimacy is dependent upon a collective audience.